An intimate encounter: DC3s empower anti-tumor CTLs : spotlight - Stojanovic, Ana; Cerwenka, Adelheid (Cancer cell, 2021)
Discrete tissue niches are emerging as essential prerequisites enabling cell communication and function in both homeostasis and disease. In a recent Cell paper, Di Pilato et al. identify a unique dendritic cell-cytotoxic T cell crosstalk within the perivascular space that facilitates T cell survival and proliferation and drives anti-tumor activity.
Gesehen am 31.01.2023